Bridging Single Neuron Dynamics to Global Brain States - Goldman, Jennifer S.; Tort-Colet, Núria; di Volo, Matteo; Susin, Eduarda; Bouté, Jules; Dali, Melissa; Carlu, Mallory; Nghiem, Trang-Anh; Górski, Tomasz; Destexhe, Alain (Frontiers in Systems Neuroscience, 2019)
Biological neural networks produce information on a background of multi-scale spontaneous activity that becomes more complex in brain states displaying higher capacities for cognition, for instance, attentive waking versus anesthetized states. Here, we review brain state-dependent mechanisms spanning ionic currents (microscale) to the dynamics of brain-wide, distributed, transient functional assemblies (macroscale). Not unlike how microscopic interactions between molecules underlie structures formed in macroscopic states of matter, using statistical physics, the dynamics of microscopic neural phenomena can be linked to macroscopic brain dynamics. Beyond spontaneous dynamics, it is observed that stimuli produce collapses of complexity, more remarkable over highly complex background dynamics present in conscious than unconscious brain states. In contrast, complexity may not be further collapsed in already low-dimensional unconscious spontaneous activity. We propose that increased complexity of spontaneous dynamics during conscious states supports responsiveness, enhancing neural networks' emergent capacity to robustly encode information over multiple scales.